2015
DOI: 10.1016/j.amc.2015.03.059
|View full text |Cite
|
Sign up to set email alerts
|

A neighborhood search function for flexible job shop scheduling with separable sequence-dependent setup times

Abstract: Multiobjective methodology for "flexible job shop" manufacturing systems production scheduling of metalmechanic sector, under a sustainability approach In the present thesis, the object of study was the productive configuration of "Flexible Job Shop" in the metal mechanics industrial sector. The configuration in question was analyzed, then, by way of theoretical fields that concern scheduling, sustainability, and multi-objective programming.Schedulling permits the estimation of makespan time in various types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…After a lot of experiments, we found that our algorithm can quickly find better solutions for cases with larger flexibility ratio (flex.) [26] which is defined as the average number of alternate machines per operation, while cases with relatively smaller flex. require more iterations and a larger initial population.…”
Section: Discussionmentioning
confidence: 99%
“…After a lot of experiments, we found that our algorithm can quickly find better solutions for cases with larger flexibility ratio (flex.) [26] which is defined as the average number of alternate machines per operation, while cases with relatively smaller flex. require more iterations and a larger initial population.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the technology can be due to the factors such as different machine and different job features. An iterated greedy algorithm is proposed for addressing the large-scale unrelated parallel machines scheduling problem (Abdelmaguid, 2015). The suggested algorithm by iterating over the constructive heuristic using destruction and construction phase provides a sequence of solutions.…”
Section: ) Unrelated Parallel Machine Scheduling Problemmentioning
confidence: 99%
“…Meta-heuristics are able to perform quite well and carry more knowledge of the problem domain, such as the ant colony optimization [13], artificial bee colony [14], artificial immune system [15], evolutionary algorithms [16], particle swarm optimization [17], tabu search [18] and variable neighborhood search [19]. Even if meta-heuristics have significantly attracted a lot of attentions from researchers, they still have two disadvantages: the first is that researchers have to design a problem-specific algorithm for each practical scheduling problem.…”
Section: Literature Reviewmentioning
confidence: 99%